Feasibility of Tunable Amplifier and Bandpass Filter for Mobile Handsets Using Active Inductor Circuits - J. Rodriguez Tellez; N. T. Ali; B. Majeed (Active and Passive Electronic Components)
In this paper active inductor circuits are employed to assess their suitability for providing a tuning function in GaAs MMIC circuits. The specifications for a mobile handset amplifier and a bandpass filter operating from a 3 V supply rail are used as test vehicles. The design and simulation of the circuits employs a low-cost commercially available low pinch-off GaAs MESFET process. The suitability of active inductors for tuning in such applications considers issues such as frequency tuning range, noise, power consumption and stability.